Odpowiedź:
[tex]a)\\\\2(3x-1)-3(2-x)=2-5(3-2x)\\\\6x-2-6+3x=2-15+10x\\\\9x-8=-13+10x\\\\9x-10x=-13+8\\\\-x=-5\ \ |\cdot(-1)\\\\x=5\\\\\\b)\\\\\frac{1}{2}(x-6)-\frac{1}{3}(3-2x)=2\frac{1}{2}x+2(\frac{1}{3}x+1)\\\\\frac{1}{2}x-3-1+\frac{2}{3}x=\frac{5}{2}x+\frac{2}{3}x+2\\\\\frac{1}{2}x+\frac{2}{3}x-\frac{5}{2}x-\frac{2}{3}x=2+3+1\\\\-\frac{4}{2}x=6\\\\-2x=6\ \ |:(-2)\\\\x=-3[/tex]
[tex]c)\\\\\frac{3x-5}{2}=\frac{5x-1}{3}\\\\3(3x-5)=2(5x-1)\\\\9x-15=10x-2\\\\9x-10x=-2+15\\\\-x=13\ \ |\cdot(-1)\\\\x=-13\\\\\\d)\\\\\frac{x+1}{5}=\frac{x-5}{2}\\\\2(x+1)=5(x-5)\\\\2x+2=5x-25\\\\2x-5x=-25-2\\\\-3x=-27\ \ |:(-3)\\\\x=9[/tex]